2009
DOI: 10.1080/10582450902816521
|View full text |Cite
|
Sign up to set email alerts
|

A Psychoneuroendocrine Perspective on the Management of Fibromyalgia Syndrome

Abstract: Objectives: Pain is a multifaceted phenomenon. Next to and in interaction with aberrations in central pain processes, behavioral factors and the neuroendocrine regulation system are also involved in pain. Our aim is to summarize neuroendocrine findings in fibromyalgia syndrome [FMS], to discuss how neuroendocrine functioning interacts with pain and psychological factors, and to confer implications of this inquiry for the management of FMS.Findings: With respect to hypothalamic-pituitary-adrenal axis functionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 68 publications
0
8
0
1
Order By: Relevance
“…Alterations in HPA functioning in fibromyalgia appear to be opposite to those seen in depression. In depression, endogenous CRH hypersecretion and blunted corticotrophin responses to exogenous CRH have been shown, while in fibromyalgia CRH hyposecretion and exaggerated corticotrophin responses to exogenous CRH were observed 7 …”
Section: Neuroendocrine Deviationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alterations in HPA functioning in fibromyalgia appear to be opposite to those seen in depression. In depression, endogenous CRH hypersecretion and blunted corticotrophin responses to exogenous CRH have been shown, while in fibromyalgia CRH hyposecretion and exaggerated corticotrophin responses to exogenous CRH were observed 7 …”
Section: Neuroendocrine Deviationsmentioning
confidence: 99%
“…Although it is possible that neuroendocrine dysregulations reflect an impairment that is constitutional or acquired due to having been exposed to trauma in the past, we recently argued that it is also possible that disturbed neuroendocrine stress responsiveness is an epiphenomenon, that is, the consequence of physiological correlates of pain, psychological distress, sleep disturbance, inactivity, and low fitness 7 …”
Section: Neuroendocrine Deviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to general adaptation syndrome theory, after being hyperreactive initially, the ANS may become hyporesponsive after prolonged stress exposure, such as with chronic pain (26). In support of this hyporesponsiveness hypothesis, studies of the chronic condition fibromyalgia have observed a hyporeactive ANS response to a range of physical stressors, including vasoconstrictor responses to cold pressor, norepinephrine and heart rate (HR) responses to exhausting physical exercise, ANS responses to orthostatic stress, and epinephrine responses to induced hypoglycemia (27). Much less is known, however, about ANS responses to psychosocial stressors in people with fibromyalgia (24,28,29).…”
Section: Introductionmentioning
confidence: 99%
“…Fibromyalgia is characterized by an amplified pain response to various physical stimuli, including pressure and temperature (McDermid et al, 1996;Berglund et al, 2002). Through various biological and behavioural mechanisms (Greenwood et al, 2003), patients with fibromyalgia may also show an increase of pain in response to emotions (Keefe et al, 2001;Zautra et al, 2001;Turk and Okifuji, 2002;Staud et al, 2004;Geenen et al, 2009). Anger may be particularly harmful in chronic pain.…”
Section: Introductionmentioning
confidence: 99%